Connections for the digital age : multimedia communications for mobile, nomadic, and fixed devices - Carne, E. Bryan, 1928- (Hoboken, N.J. : John Wiley & Sons, 2011)
'Most notably used for computer screens and televisions, LCDs (liquid crystal displays) are a widely used technology. Providing both an historical and business-minded context, this extensive resource describes the unique scientific and engineering techniques used to create LCDs. The history of the science and technology behind the LCD is described in a prelude to the development of the device, presenting a rational development theme and pinpointing innovations. Additionally, the book illustrates how mathematics, physics, and chemistry are put to practical use in the LCDs we use everyday. Everyone from science students to engineers and product designers will find this engaging work valuable'--
Includes bibliographical references and index.
Keywords: Multimedia communications